Internal Factors Approach to Improve Hospital Nurse Performance in Developing Countries: Systematic Review - Zefrial, Y (KnE Life Sciences, 2018)
The world is having serious challenge in variations in health problems and also the increasing of population. On the other hand, there is a critical problem of workforce shortage in the health system. These challenges will have greater impact on developing countries, who have large population and shortage of health work-force personnel. One of the strategies in handling the problem of the shortage of health workers is the performance improvement strategy of health personnel. The aim of the study is to find the best approaches to improve the performance of hospital nurses in developing countries. The author searched databases such as ProQuest, Springer, EBSCO Host, Science Direct, Jurnal Kesmas, and Jurnal UGM in accordance with the present research questions. The authors independently review the articles by applying inclusion and exclusion criteria. The articles included in the study discuss about the nurses in hospitals of developing countries and their performance outcome criteria. The study found 392 articles that were related to the research topic and 24 articles that were related in titles and abstracts. After the full-text assessment of the 24 articles, it was found that 4 (four) articles met the inclusion criteria. The included articles are aimed to measure impact of interventions to the job performance of nurses. The study found that the sample and the data analysis used in the articles are varied. The conclusion of the study by using systematic review indicated that the variable that affect the performance of nurses consist of external and internal factors. Developing countries can use the internal factors approach to improve the performance of the hospital nurses. Keywords: nurse performance, internal factors approach, PICOs, hospital